THE POTENTIALS OF NARROW READING TO ADVANCE L2 PROFICIENCY - Ayu Chrismonica Islami (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
Narrow reading is a subset of extensive reading which is considered as a good narrow input for language acquirer. It is believed that by reading, language acquirer frequently absorbs meaning and knowledge. The object of this study was to reveal the potential of narrow reading to advance second language proficiency. This study was carried out by analyzing individuals autobiographical narrative writing with 2 informants who were identified to be avid readers who read for certain times (in this case, 12 months or longer), and read books in certain genre. It was conducted for 4 months to compile the narrative writing and the individuals’ personal data. From the findings, it was shown that the key benefit of narrow reading is the enrichment of vocabulary which leads to advance second language proficiency.